2011
DOI: 10.1039/c0an00829j
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin 6 and 1,6-diphenyl-1,3,5-hexatriene (DPH) as fluorescent probes to monitor protein aggregation

Abstract: We report the use of Coumarin 6 and 1,6-diphenyl-1,3,5-hexatriene (DPH) for the identification of protein aggregates for the first time. The two dyes can be used at very low (nanomolar) concentrations and do not interfere with the aggregation process, as is reported for other commonly used fluorescent protein probes. In the presence of protein aggregates, their quantum yields are significantly high. DPH is able to recognize both amorphous and fibrillar aggregates but cannot distinguish between them. Coumarin 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 46 publications
3
22
0
Order By: Relevance
“…To validate this, an apolar-sensitive probe, 1,6-diphenyl-1,3,5-hexatriene (DPH, λ em = 428 nm), was anchored on the vesicular wall to detect the change of hydrophobic region. [20] As expected, the fluorescence produced a dramatic jump over time ( Figure S4, Supporting Information), verifying our viewpoint on ATPinduced hydrophobic change. In addition, noting that both the initial and final sacs are stable over two weeks without fission or fusion, suggesting that this expansion is indeed attributed to the membrane extension of single microcapsule ( Figure S5, Supporting Information).…”
Section: Polymer Design and Vesicular Self-assemblysupporting
confidence: 85%
“…To validate this, an apolar-sensitive probe, 1,6-diphenyl-1,3,5-hexatriene (DPH, λ em = 428 nm), was anchored on the vesicular wall to detect the change of hydrophobic region. [20] As expected, the fluorescence produced a dramatic jump over time ( Figure S4, Supporting Information), verifying our viewpoint on ATPinduced hydrophobic change. In addition, noting that both the initial and final sacs are stable over two weeks without fission or fusion, suggesting that this expansion is indeed attributed to the membrane extension of single microcapsule ( Figure S5, Supporting Information).…”
Section: Polymer Design and Vesicular Self-assemblysupporting
confidence: 85%
“…The therapeutic effects of the drug loaded NPs would depend on the uptake of the particles by cancer cells (Hong et al., 2019 ). Coumarin 6 (C-6) is a fluorescent probe, which was used to represent the particles internalized the cells (Makwana et al., 2011 ). TAB-CIS/5-FU LPHNs showed higher uptake than that of CIS/5-FU LPHNs, which revealed that the LBL NPs had excellent ability to enter cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Coumarin-containing trifunctional probe 137, assembled using a cleavable linker, is useful for efficient enrichment and detection of glycoproteins (Tsai et al, 2010). Coumarin 6 has been used as a fluorescent probe to monitor protein aggregation and can distinguish between both amorphors and fibrillar aggregates (Makwana et al, 2011). An S N Ar reaction-triggered fluorescence probe is developed using a new fluorogenic compound derivatized from 7-aminocoumarin for oligonucleotides detection (Shibata et al, 2009).…”
Section: Coumarin-derived Fluorescent Chemosensors For Enzymesmentioning
confidence: 99%